1991
DOI: 10.1016/0735-1097(91)90505-4
|View full text |Cite
|
Sign up to set email alerts
|

High speed rotational coronary atherectomy for patients with diffuse coronary artery disease

Abstract: High speed rotational coronary atherectomy was undertaken using the Rotablator in 42 patients who were suboptimal candidates for balloon angioplasty. Most patients (71%) had diffuse coronary artery disease, defined as a stenosis greater than 1 cm in length. Previous restenosis after balloon angioplasty was present in 21% and 10% had an ostial lesion. Adjunctive balloon angioplasty was not used to reduce residual stenosis after atherectomy. The procedure was successful in 76% of patients. Procedural success was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 25 publications
2
44
1
4
Order By: Relevance
“…[1][2][3][4] During ablation of the plaque, microparticles are produced by the advancing burr and experimental studies suggested that these particles pass harmlessly through the distal microcirculation. 10,19 However, several clinical studies have shown that RA is associated with higher rates (6-15%) of the no-reflow/slow-flow phenomenon than other coronary revascularization procedures, [5][6][7][8][9] and this phenomenon can lead to serious ischemic complications, such as conduction disturbances, myocardial infarction, cardiogenic shock or even death.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] During ablation of the plaque, microparticles are produced by the advancing burr and experimental studies suggested that these particles pass harmlessly through the distal microcirculation. 10,19 However, several clinical studies have shown that RA is associated with higher rates (6-15%) of the no-reflow/slow-flow phenomenon than other coronary revascularization procedures, [5][6][7][8][9] and this phenomenon can lead to serious ischemic complications, such as conduction disturbances, myocardial infarction, cardiogenic shock or even death.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many new devices now in use, rotational atherectomy is unique in its ability to mechanically ablate hard fibro-calcific tissue without inducing significant trauma to less diseased vessel segments [1][2][3][4][5]. In contrast to other atherectomy devices which are limited by vessel size and rigidity, PTCRA is well-suited for use in a variety of arteries including those that are diffusely diseased, calcified, and small in caliber; vessels not effectively treated with balloon angioplasty or stents [1,5,7,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, non-randomized reports demonstrate that PTCRA can be performed safely and with a high degree of success in both simple and complex coronary disease [7][8][9]12,[14][15][16][17][18]31,32]. The PTCRA Registry demonstrated Ͻ2% incidence of emergent bypass and Ͻ1% incidence of Q wave infarction and death [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, experimental studies suggest that microparticle dimensions are dependent on the size of the burr and the speed of rotation, and it is generally assumed that in human coronary use, the majority of microparticles are less than 5 gm in diameter.12 Al-though particles of this size should pass harmlessly into the microcirculation, distal embolization leading to myocardial infarction has been reported. 13 The relative contribution of tissue pulverization versus the "Dotter" effect (mechanical dilation of the lesion) is unknown.…”
Section: Mechanism Ofactionmentioning
confidence: 99%